On the Way to SD-WAN Solution - Stanislav V. Korsakov; Valery A. Sokolov (Моделирование и анализ информационных систем, 2019)
The article describes a background and some steps in the implementation of an industrial solution to build manageable mesh overlay network on top of a complete or partially non-manageable underlay network. The overlay network has (or may have) some features from the software defined networks world. We call this solution as SD-WAN Lite to highlight that this solution is not (and will not be in a visible future) a complete SD-WAN solution.